Connecting organizational silos taking knowledge flow management to the next level with social media - Leistner, Frank (John Wiley & Sons, 2012)
Practical guidance on how to successfully introduce enterprise social networks to connect employees While there are a fast growing number of books around social media and enterprise 2.0, the focus is often on the technical tools. Connecting Organizational Silos approaches social media and enterprise 2.0 from a knowledge flow management perspective. It offers practical and specific guidance on what to do and what not to do when introducing social media in an organization. This concise, easy-to-read guide offers a nuts-and-bolts look at how to get started in social media and drive it to success.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher. - Print version record
Keywords: Knowledge management; Social media; Knowledge Management; Social Media; Gestion des connaissances; Médias sociaux; social media; BUSINESS & ECONOMICS; Information Management; BUSINESS & ECONOMICS; Knowledge Capital